(3UhQI GdTQb GdCOfi GdESdGei ai cJH GdQMdGJ GddGJjfjI Ref GdMQcI GdUdjHjI (B491-690(3g`(B/1098-1291(3e(B/ s - (3CMeO eMeO EHQGgje eYQhas; (3YHOGdMGaX YHOGdNGdb GdHfG (B: s; (3jSQi CMeO RjOGf (B: s ((3GdbGgQI (B: s (3CMeO eMeO EHQGgje eYQha (B: s, 2016)
(3JfGhd GdJegjO GdYhGed GdMGceI dEfJGL UhQI GdeSdejf ai cJH GdQMdGJ GddGJjfjI(B: (3Ke LGA GdHGH GdChd HYfhGf(B: "(3UhQI GdESdGe h GdChVGY GdOjfjI ddeSdejf ef NdGd cJH GdQMdGJ GddGJjfjI(B": (3Ke GdHGH GdKGfi HYfhGf(B: "(3UhQI GdChVGY GdSjGSjI h GdYScQjI ai GdTQb GdCOfi GdESdGei ef NdGd cJH GdQMdGJ GddGJjfjI(B": (3Ke GdHGH GdKGdK JMJ YfhGf(B: "(3UhQI GdChVGY GdMVGQjI ai GdTQb GdCOfi GdESdGei ef NdGd cJH GdQMdGJ GddGJjfjI(B". (3Cge GdfJGFL GdJWHjbjI GdJi Je GdJhUd EdjgG(B: (3XgQJ UhQI GdESdGe ai cJH GdQMdGJ GddGJjfjI HTcd SdHi(B: (3HjfeG JfhYJ UhQI GdMjGI GdOjfjI ddeSdejf Hjf eG gh SdHi h eG gh EjLGHi h eG gh eMGjO dG jMed MceG(B. (3JYO UhQI GdOhd GdESdGejI h McGegG SjFI HTcd YGe(B: (3dcf UhQI GdJfXjeGJ GdYScQjI ddeSdejf HOJ eMGjOI Edi MO cHjQ(B. (3Ydi GdUYjOjf GdGbJUGOi h GdGLJeGYi XgQ GdeSdehf Ydi fMh eMGjO(B: (3eY hLhO HYV GdMGdGJ GdGSJKfGFjI GdJi TgOJ MVhQG SdHjG h BNQ EjLGHjG(B. (3Ydi hLg GdNUhU de JTgO GdLhGfH GdSdHjI ef UhQI GdeSdejf h eG jNUge JMSfG eWQOG Ydi eOGQ MbHI GdMQhH GdUdjHjI(B. (3CeG GdLGfH GdPi JMSf aYdG eY fgGjI MbHI GdMQhH GdUdjHjI agh eYdheGJ GdQMGdI GddGJjf Yf GdeSdejf h eG jNUge(B: (3ai Xd JQGce eYQai RGOJ JaGUjdg eY Whd GdGMJcGcs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdJGQjN GdESdGei h GdMVGQI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdUhQI GdPgfjIs; (3GdeSdehf h ChQHGs; (3UhQI GdeSdejfs